14-Bit Fully Differential SAR ADC with PGA Used in Readout Circuit of CMOS Image Sensor. (23rd February 2021) - Zhang, Xiaowei; Fan, Wei; Xi, Jianxiong; He, Lenian
Abstract : This paper proposes a 14-bit fully differential Successive Approximation Register (SAR) Analog-to-Digital Converter (ADC) with a programmable gain amplifier (PGA) used in the readout circuit of CMOS image sensor (CIS). SAR ADC adopts two-step scaled-reference voltages to realize 14-bit conversion, aimed at reducing the scale of capacitor array and avoiding using calibration to mitigate the impact of offset and mismatch. However, the reference voltage self-calibration algorithm is applied on the design to guarantee the precision of reference voltages, which affects the results of conversion. The three-way PGA provides three types of gains: 3x, 4x, and 6x, and samples at the same time to get three columns of pixel signal and increase the system speed. The pixel array of the mentioned CIS is 1026 × 1024, and the pixel pitch is 12.5 μ m × 12.5 μ m . The prototype chip is fabricated in the 180 nm CMOS process, and both digital and analog voltages are 3.3 V. The total area of the chip is 6.25 × 18.38 mm 2 . At 150 kS/s sampling rate, the SNR of SAR ADC is 71.72 dB and the SFDR is 82.91 dB. What is more, the single SAR ADC consumes 477.2 uW with the 4.8 V PP differential input signal and the total power consumption of the CIS is about 613 mW.